PENGARUH PRAKTIK INDUSTRI, PROGRAM KEAHLIAN DAN MOTIVASI TERHADAP KESIAPAN KERJA SISWA SMK NEGERI KOTA SURAKARTA - Sidiq, Ahmad (Riset Manajemen dan Akuntansi, 2023)
As a researcher on the work readiness of students after graduating from school, the researcher tried to carry out research in the city of Surakarta at 9 vocational schools with various available competencies. This research uses primary data obtained from field observation data, and data obtained from questionnaires as well as documentation data from the questionnaire. Data analysis uses multiple linear regression in this research which has more than 1 independent variable and one dependent variable. With a multiple linear regression equation in the following form: Y= b1X1 + b2X2+ b2X3+ e1. Work practices, skills and motivation programs have a positive and significant effect on the work readiness of class XII State Vocational School students in the city of Surakarta. The higher the skills possessed by Surakarta City State Vocational School students.